Risk factors of hepatitis C virus infection in blood donors in Thailand: A multicenter case-control study - Tawesak Tanwandee (2018)
Objective: To investigate the risk of hepatitis C virus (HCV) infection in healthy blood donors in Thailand Material and Method: We performed a case-control study of 435 HCV-seropositive blood donors and 894 HCV-seronegative blood donors as controls. The study was done with direct interview regarding demographic characteristics and risk factors. Odds ratios (OR) with 95% confidence intervals (Cls) were calculated by using conditional logistic regression. Results: The final multivariable model included only the following independent HCV risk factors: intravenous drug user (IDU) (OR = 61.5; 95%CI, 26.6-142.5), previous blood or blood products transfusion (OR = 12.3; 95%CI, 7.6 -19.9), sharing of razors (OR = 2.3, 95%CI, 1.6-3.2),unsafe injection (OR = 3.3, 95%CI, 1.8-5.9), unused condom (OR = 1.6; 95%CI, 1.1, 2.4). No risk was shown for a history of tattoo, ear piercing, or acupuncture and multiple sexual partners. Conclusion: The risk factors for HCV infection in healthy blood donors in Thailand are IDU, past history of blood transfusion and unsafe injection.